Meningkatkan Self Esteem Korban Bulliying melalui Teknik Assertive Training - Faizatul Musyarofah; Wawan Juandi (Fakultas Dakwah Universitas Ibrahimy, 2021)
Islamic boarding schools are salaf educational institutions that uphold the values ​​of akhlaq al-karimah. However, it is very unfortunate, in the pesantren there is also bullying experienced by a student who has physical retardation and a slow way of thinking. Bullying received by the victim in the form of insults, ridicule and ridicule. The bullying causes the victim's self-esteem to decrease so that the victim tends to withdraw from the environment and is afraid to mingle with his friends. The condition of low self-esteem can be seen from the scale score given by the researcher to the counselee before the action is taken, namely 36. The score belongs to the category of low self-esteem. This study aims to increase the self-esteem of victims of bullying by using assertive training techniques. The research method used is action research. The results showed that the condition of the victim's self-esteem increased although not significantly after the action in cycle I. The score from the given scale was 61, the score was included in the category of moderate self-esteem. In the reflection of the first cycle, the counselor prepares for better treatment in the second cycle, until a score of 89 is obtained on the scale given by the counselor to the counselee after handling the second cycle. From the data obtained, it can be concluded that the self-esteem of victims of bullying can be increased by using assertive training techniques